2018
DOI: 10.1039/c8ra04825h
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional mesoporous calcium carbonate–silica frameworks thermally activated from porous fossil bryophyte: adsorption studies for heavy metal uptake

Abstract: In this paper, three-dimensional mesoporous calcium carbonate-silica frameworks have been created from the straw tufa (ST) originating from porous fossil bryophyte by a thermal activation technique. A batch of adsorption kinetic and thermodynamic experiments were used to investigate the adsorption capacity of Cd (II) The adsorption capacities of Cd(II) and Pb(II) both decrease with the addition of the other heavy metal cations, indicating that the adsorption is hindered by the competitive adsorption and the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…S4(a), † the doublet characteristics of Cd appeared at 406 and 412 eV were in line with those of Cd(OH) 2 , which indicated the precipitation form of cadmium. 20,46 Combined with XRD pattern, it is clear that in this study, the removal of Cd(II) from aqueous solution was mainly conducted by surface-induced precipitation as hydroxides. Notably, the peaks of Fe 2p were impaired aer Cd(II) adsorption ( Fig.…”
Section: Removal Mechanismmentioning
confidence: 86%
“…S4(a), † the doublet characteristics of Cd appeared at 406 and 412 eV were in line with those of Cd(OH) 2 , which indicated the precipitation form of cadmium. 20,46 Combined with XRD pattern, it is clear that in this study, the removal of Cd(II) from aqueous solution was mainly conducted by surface-induced precipitation as hydroxides. Notably, the peaks of Fe 2p were impaired aer Cd(II) adsorption ( Fig.…”
Section: Removal Mechanismmentioning
confidence: 86%
“…Over the entire study period, the slight basicity and probably reducing character of these open waters over all the study period would have been favorable for the solubilization in them of the trace metals studied by their release from Fe and Mn (oxy)hydroxides on the particulate phases [12,13] and; from the mineralization of the relative important particulate organic matter in the form of soluble organometallic complexes [4;10] , particularly from the degradation of macrophytes of the genus Eicchornia crassipes [45] . The same would have been true for their relatively important salinity and conductivity [4;16,17] , and of the solubilization of other trace metals than Cd, Ni, Pb, and Zn from carbonates on the particulate phases [10,11] . These processes would explain the relative important trace metal contents of these open waters over the entire study period, despite the retention of these trace metals on the particulate phase by sulphides [8,9] and organic matter [4;10] .…”
Section: Discussionmentioning
confidence: 99%
“…The pH, temperature, salinity, conductivity, as well as dissolved oxygen, organic matter, carbonates, sulphide, Fe, and Mn contents, of the open waters at water-sediment interface play an important role in the dynamics of trace metals. In neutral to basic and reducing aquatic environments, trace metals are immobilized on the particulate phase by sulphides and carbonates [8][9][10][11] ; while Fe and Mn (oxy)hydroxides promote their solubilization in these conditions [12,13] . In acidic to neutral and oxidizing aquatic environments, the reverse of these reactions takes place.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the International Union of Pure and Applied Chemistry (IUPAC) classification, the ZnCl325 and ZnCl350 activated carbons belonged to typical type IV adsorption isotherms with an H1 hysteresis loop characteristic of mesoporous structures (Figure 4) [20]. In addition, as seen in Figure 5, it was observed that the BET surface area increased proportionally with high relative pressure (p/p0) [21].…”
Section: Bet Analysismentioning
confidence: 93%